Analisis Tingkat Kepuasan Penggunaan Aplikasi E- Faktur Pajak dalam Proses Pelaporan Pajak di PT. Anugerah Texindotama - Shan Putra Elliotman Sarumaha; Agus Budiyantara (Asosiasi Profesi Telekomunikasi dan Informatika Indonesia, 2024)
This study aims to analyze the level of satisfaction with the use of the tax e-Faktur application in the tax reporting process at PT Anugerah Texindotama. The e-Faktur application is a technological innovation that facilitates electronic tax reporting, which is expected to increase compliance and efficiency in the tax administration process. This research method includes observation, interviews, and distributing questionnaires to 43 respondents who are directly related to the use of the application. Based on the results of the study, it was found that the use of the e- Faktur application has had a positive influence on user satisfaction, with an average satisfaction level of 80.83%, which is categorized as good. Several advantages of the application, such as minimizing the risk of errors and ease of access, also increase user acceptance. However, there are technical constraints that need to be improved to support system optimization. Recommendations for improvement focus on enhancing features and technical training for employees to strengthen the implementation of the e-Faktur application in corporate tax reporting.